Translation theory and the Old Testament in Matthew : the possibilities of Skopos theory - Chung, W. (Linguistic Biblical Studies, 2017)
In Translation Theory and the Old Testament in Matthew , Woojin Chung employs a rigorous method of Skopos theory to examine Matthew's citation technique in his infancy narrative and locates the specific purpose of his use of Scripture. He argues that the complex nature of the formulaic quotations and allusion in Matthew 1‒2 can be understood in light of new methodological insights. The way Matthew cites the Old Testament for his communicative purpose is congruent to the approach of a Skopos translator who is motivated by a specific purpose of translation. The theory of interpretation of his use of Scripture, therefore, can be informed by the theory and method of translation.